2017
DOI: 10.1111/cobi.12837
|View full text |Cite
|
Sign up to set email alerts
|

The value of virtual conferencing for ecology and conservation

Abstract: Abstract:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 18 publications
1
82
0
1
Order By: Relevance
“…Because most scientific journals expect novelty in the work they accept for publication, these high publication rates can help refute recent criticism (Kircherr & Biswas ) that academic conferences are failing to deliver novel content despite their increasing costs and environmental footprints (Fraser et al. ). However, we analyzed a single conference.…”
Section: Discussionmentioning
confidence: 99%
“…Because most scientific journals expect novelty in the work they accept for publication, these high publication rates can help refute recent criticism (Kircherr & Biswas ) that academic conferences are failing to deliver novel content despite their increasing costs and environmental footprints (Fraser et al. ). However, we analyzed a single conference.…”
Section: Discussionmentioning
confidence: 99%
“…Fraser et al (2017) rightly conclude that global virtual conferencing is possible for fields like conservation biology. These have been investigated by IMCC delegates in discussion sessions at OceansOnline, an affiliate conference of IMCC4, with a result of organizers subsequently looking to offer telepresence as an option for the forthcoming 5th International Marine Conservation Congress (Thaler, 2017).…”
Section: Overcoming the Limitations Of In-person Attendance At Confermentioning
confidence: 98%
“…These have been investigated by IMCC delegates in discussion sessions at OceansOnline, an affiliate conference of IMCC4, with a result of organizers subsequently looking to offer telepresence as an option for the forthcoming 5th International Marine Conservation Congress (Thaler, 2017). Yet, Fraser et al (2017), while additionally noting the virtual approach's susceptibility to technical difficulties, are also among the scientists that cannot get past the social limitations virtual conferences impose. Psychology, management, and communications studies have shown that information exchange, collaboration, and networking multiply during face-to-face meetings (Duffy and McEuen, 2010).…”
Section: Overcoming the Limitations Of In-person Attendance At Confermentioning
confidence: 99%
“…Moreover, as social role models, their behavior may influence others' intentions to change their own behavior [11,12]. Finally, in terms of the rationale of the study, although there is research concerning the institutional factors that hinder reductions in academic air travel [11,[13][14][15][16][17], research concerning individual-level processes relating to flight reduction is scant [9,18].A variety of individual-level theories are available for helping to explain attitude-behavior gaps. Here we use the theory of cognitive dissonance, as it is arguably the most specifically applicable approach for understanding dissonance per se.…”
mentioning
confidence: 99%